CONTACT METAMORPHISM AND METASOMATISM NEAR THE TALNAKH INTRUSION: FLUID CONVECTION AND HEAT TRANSFER MODELING ON THE BASIS OF THE FINITE-DIFFERENCE METHOD - Polyansky O.P.; Reverdatto V.V. (My University, 2006)
The zonal contact-metamorphic aureoles around intrusions provide insight into the thermal impact of magma on country rocks. The issue of conductive heating of rocks without the participation of fluid was scrutinized. The duration of cooling and temporal temperature distribution versus distance from the contact were estimated. However, in many cases, the conductive heat transfer turns out to be insufficient to form thick complexes of thermally metamorphosed rocks. As was shown for a number of geological and theoretical models, convective heat-and-mass transfer near magmatic bodies is of great importance.
Keywords: Noril’sk ore distric; Talnakh intrusion